2014
DOI: 10.1111/tbed.12194
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Seroprevalence of Foot and Mouth Disease in Sheep and Goats in Punjab, Pakistan

Abstract: Foot and mouth disease (FMD) is a highly contagious disease of ruminants that causes huge economic losses around the globe. However, the prevalence of FMDV in small ruminants has been overlooked in Pakistan. A seroepidemiological study was conducted in Chakwal, Faisalabad and Khanewal districts of Punjab, Pakistan to determine the prevalence of FMD in sheep and goats. A total 1200 serum samples were collected from sheep (n = 180) and goats (n = 920) and were subjected to 3ABC non-structural protein enzyme-link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 7 publications
3
9
1
Order By: Relevance
“…The country sero-prevalence of FMD in SR was found to be 22.5% similar to what has been reported in other countries where FMD is endemic [ 16 , 17 ]. It is however higher than that reported in Ethiopia, Israel, Libya and Sudan [ 8 , 9 , 11 , 12 , 18 ] but about half of what has been reported in Tanzania and Myanmar [ 14 , 19 , 20 ].…”
Section: Discussionsupporting
confidence: 85%
“…The country sero-prevalence of FMD in SR was found to be 22.5% similar to what has been reported in other countries where FMD is endemic [ 16 , 17 ]. It is however higher than that reported in Ethiopia, Israel, Libya and Sudan [ 8 , 9 , 11 , 12 , 18 ] but about half of what has been reported in Tanzania and Myanmar [ 14 , 19 , 20 ].…”
Section: Discussionsupporting
confidence: 85%
“…In this study the country sero-prevalence of FMD in SR was found to be 23.3% similar to what has been reported in other countries where FMD is endemic [41,42]. It is however higher than that reported in Ethiopia, Israel, Libya and Sudan [33,34,36,37,43] but about half of what has been reported in Tanzania and Myanmar [39,44,45].…”
Section: Discussionsupporting
confidence: 85%
“…The environment in which sheep and goats were raised was poor and represents a stress factor on the animals. Bad housing and the nutritional deficiency facilitate the spread of contagious diseases [ 38 ].…”
Section: Resultsmentioning
confidence: 99%